2021
DOI: 10.51731/cjht.2021.230
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness and Guidelines for Opioid Substitution Treatment

Abstract: There was evidence indicating that in the treatment of opioid use disorder, injectable hydromorphone, or injectable methadone provided more benefit at less cost compared with injectable diacetylmorphine over a 6-month time horizon. Evidence suggests that in the treatment of opioid use disorder, both injectable hydromorphone and injectable diacetylmorphine are likely to provide more benefit at less cost than methadone maintenance treatment. Treatment with injectable hydromorphone was more cost-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 12 publications
1
28
0
2
Order By: Relevance
“…While the effectiveness of naloxone toward reversing opioid-induced respiratory depression has been demonstrated since its approval by the US Food and Drug Administration (FDA) in 1971, its therapeutic limitations have become more pronounced in recent years following the advent of pervasive new synthetic opioid analogs. The primary shortcoming of naloxone is its rapid conversion in vivo to the highly polar 3-glucuronide conjugate 3 , an inactive phase II metabolite (Figure ), resulting in a short circulatory half-life ranging from 30 to 120 min . Synthetic opioids such as fentanyl exhibit significantly longer half-lives by comparison, as they are believed to be less vulnerable to metabolic degradation due to their high receptor affinities and greater propensity to absorb into adipose tissue. As a consequence, victims of synthetic opioid poisoning rescued with a single dose of naloxone may experience a recurrence of opioid toxicity and severe respiratory depression known as renarcotization.…”
mentioning
confidence: 99%
“…While the effectiveness of naloxone toward reversing opioid-induced respiratory depression has been demonstrated since its approval by the US Food and Drug Administration (FDA) in 1971, its therapeutic limitations have become more pronounced in recent years following the advent of pervasive new synthetic opioid analogs. The primary shortcoming of naloxone is its rapid conversion in vivo to the highly polar 3-glucuronide conjugate 3 , an inactive phase II metabolite (Figure ), resulting in a short circulatory half-life ranging from 30 to 120 min . Synthetic opioids such as fentanyl exhibit significantly longer half-lives by comparison, as they are believed to be less vulnerable to metabolic degradation due to their high receptor affinities and greater propensity to absorb into adipose tissue. As a consequence, victims of synthetic opioid poisoning rescued with a single dose of naloxone may experience a recurrence of opioid toxicity and severe respiratory depression known as renarcotization.…”
mentioning
confidence: 99%
“…Impairment of lymphatic transport by Klienhan’s transport index is found in 47% and 63% of patients with lipedema, [ 4 , 6 ] but lipedema remains distinct from lymphedema in that the lymphatic system is not obstructed. Bioimpedance spectroscopy studies found increased extracellular water, magnetic resonance imaging (MRI) of lipedema LCT demonstrated increased sodium content and extracellular fluid, but ultrasound did not show free fluid as in lymphedema, consistent with increased fluid and sodium bound to GAGs in the extracellular matrix [ 5 , 7 9 ]. All patients with lymphedema have abnormal lymphatic function, which closely corelates with their disease progression and severity.…”
Section: Backgrondmentioning
confidence: 99%
“…Generally, cosmetic suction lipectomy is performed on healthy individuals with normal lymphatic function who are close to ideal weight. A derivative or modification of suction lipectomy procedures that use cannulas attached to suction to remove adipose and other subcutaneous tissue components are also increasingly used as a medically necessary non-cosmetic surgical treatment of lymphedema [ 12 ] and lipedema [ 9 ]. The application of suction cannulas for these diseases removes not only subcutaneous adipose tissue but also other LCT components, including extracellular proteins and GAGs.…”
Section: Backgrondmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, medical cannabidiol 3% is suggested as a potential treatment for the BPSD in general [ 24 ], and irritability in PwD. However, the mechanism of cannabidiol is not well elucidated, and there is much clinical evidence of its effectiveness [ 25 ]. Furthermore, the cholinesterase inhibitors have shown some positive results in the treatment of irritability, however their side effects should be well considered [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%